2000
DOI: 10.1002/pc.10223
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenological study of the mechanical properties of long‐fiber filled injection‐molded thermoplastic composites

Abstract: Tensile and flexural tests on specimens cut from rectangular injection‐molded plaques show that long‐fiber filled thermoplastic composites are complex, non‐homogeneous, anistropic material systems. Like all fiber‐filled materials, they exhibit through‐thickness nonhomogeneity as indicated by differences between tensile and flexural properties. The in‐plane orientation of fibers in through‐thickness layers causes the material to have in‐plane anisotropic properties. However, these long‐fiber filled materials ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…However, long glass fibres (LGF) are used more and more often as a reinforcement, since it is known that longer fibres with the same fibre diameter (i.e. with higher fibre aspect ratio) provide higher stiffness, tensile strength and toughness compared to shorter ones [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, long glass fibres (LGF) are used more and more often as a reinforcement, since it is known that longer fibres with the same fibre diameter (i.e. with higher fibre aspect ratio) provide higher stiffness, tensile strength and toughness compared to shorter ones [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…existence of a fountain flow) [5], the core layer is thicker when the fibre length increases [6,7,12]. In addition, other studies have shown that whatever is the reinforcement length (short or long) the skin layers thickness remains roughly the same whereas the core layer thickness increases when the cavity thickness is higher [13,14]. This typical multi-layered structure also greatly influences the mechanical performances of the manufactured parts [10].…”
Section: Introductionmentioning
confidence: 99%
“…produce flow perturbations and weld lines and act on the material anisotropy and heterogeneity. 6,13,27 Mechanical properties increase requires both the control of the fiber reinforcement orientation and the improvement of its efficiency (increase of fiber/matrix interface quality and fiber aspect ratio). 25,28−31 The strength of composite materials based on discontinuous fibers depends on both the interfacial shear strength and the matrix strength.…”
mentioning
confidence: 99%